Driving down memory lane: The influence of memories in a community following organizational demise. Issue 9 (September 2019) - Do, Boram; Lyle, Matthew C. B.; Walsh, Ian J.
In this paper, we explain how defunct organizations influence the communities they leave behind through ongoing processes of communal memory work, a twofold social process through which members of collectives develop shared memories of a defunct organization and behaviorally engage with its mnemonic traces. We explore how individuals' shared construal of their environment shapes their emotional orientation towards their past, which in turn gives rise to particular forms of memory work. We further show how communal memory work influences changes in an organization's role in a community's identity and members' construal of their environment. We develop our theory through an analysis of a case study of South Bend, Indiana, in the 54 years following the closure of the Studebaker Corporation's automotive factory in 1963. We close by discussing the implications of this work for memory scholarship.